Preparation of O′-Sialon-based ceramics by two-stage liquid phase sintering and study on the toughening mechanism of ultrafine-grained sintered clusters. Issue 7 (1st April 2022) - Xi, Chenyang; Guo, Haoshan; Zhang, Chunxiang; Luo, Junting
Abstract: Ultrafine-grained O′-Sialon-based ceramics were prepared by two-stage sintering at 1250 °C, with large particle GH4169 superalloy powder and nano Al2 O3 –Y2 O3 as composite sintering aids. The effects of these aids on the densification, microstructure, and mechanical properties of O′-Sialon-based ceramics during two-stage sintering were also studied. Studies have shown that the densification process of O′-Sialon-based ceramics promoted by composite sintering additives, presents with the characteristics of two-stage liquid-phase sintering. In the first stage, GH4169 formed ultrafine-grained sintered clusters in the sintered material through liquid phase diffusion. In the second stage, the uniformly dispersed nano Al2 O3 –Y2 O3 realized the uniform sintering of the material. In the fracture process, the ultrafine-grained sintered clusters hindered the crack propagation and promoted multiple deflections of the crack around the edge of the clusters, achieving the effect of crack deflection toughening. This effect, dominated by ultrafine-grained sintered clusters, significantly improved the fracture toughness of O′-Sialon-based ceramics up to 8.52 MPa m 1/2 .